2020
DOI: 10.1038/s41598-020-72715-y
|View full text |Cite
|
Sign up to set email alerts
|

A non-lethal method for detection of Bonamia ostreae in flat oyster (Ostrea edulis) using environmental DNA

Abstract: Surveillance and diagnosis of parasitic Bonamia ostreae infections in flat oysters (Ostrea edulis) are prerequisites for protection and management of wild populations. In addition, reliable and non-lethal detection methods are required for selection of healthy brood oysters in aquaculture productions. Here we present a non-lethal diagnostic technique based on environmental DNA (eDNA) from water samples and demonstrate applications in laboratory trials. Forty oysters originating from Limfjorden, Denmark were ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…eDNA has been studied extensively since the 2000s with numerous applications, such as metagenomics, species detection, or biomass estimation ( 1 , 2 ). Aquatic animal pathogens are basically waterborne; therefore, eDNA has been studied as a potential tool for monitoring aquatic animal diseases in aquaculture ( 3 5 ) and border control ( 6 , 7 ). Although the term “eDNA” has not been used in fish virus research, eDNA could be applied in monitoring waterborne viruses in combination with virus concentration techniques.…”
Section: Introductionmentioning
confidence: 99%
“…eDNA has been studied extensively since the 2000s with numerous applications, such as metagenomics, species detection, or biomass estimation ( 1 , 2 ). Aquatic animal pathogens are basically waterborne; therefore, eDNA has been studied as a potential tool for monitoring aquatic animal diseases in aquaculture ( 3 5 ) and border control ( 6 , 7 ). Although the term “eDNA” has not been used in fish virus research, eDNA could be applied in monitoring waterborne viruses in combination with virus concentration techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we have demonstrated that eDNA barcoding can be employed to characterize the species composition of captured fish from the meltwater leftover in industrial and artisanal fishing operations. eDNA is gaining popularity and utility in fisheries and seafood research and has the potential to be a potent and complementary tool to the growing number of approaches to improving traceability throughout the seafood supply chain [ 38 , 40 , 54 , 55 ]. Built upon nearly two decades of studies applying the well-vetted concept of DNA barcoding to identify fish to species level [ 16 , 56 ], the eDNA approach is positioned to be both a familiar and a transformative tool in improving seafood monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of single species detection, eDNA is subjected to amplification with species-specific primer [ 44 ]. Here, conventional PCR (cPCR) can be used to conduct a ‘presence and absence’ study whereas quantitative PCR (qPCR) is more preferred for quantification of targeted DNA and elimination of false positive or negative results [ 16 , 45 ].…”
Section: Overview Of Sampling and Laboratory Protocol For Ednamentioning
confidence: 99%
“…Recently, CRISPR-Cas is gaining popularity in eDNA-based species detection [ 46 ]. Moreover, in all cases, positive and negative controls should be maintained [ 44 ].…”
Section: Overview Of Sampling and Laboratory Protocol For Ednamentioning
confidence: 99%
See 1 more Smart Citation